2012
DOI: 10.1590/s1519-69842012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nickel on the fern Regnellidium diphyllum Lindm. (Marsileaceae)

Abstract: The heterosporous fern Regnellidium diphyllum occurs in southern Brazil and some adjoining localities in Uruguay and Argentina. Currently it is on the list of threatened species in the state of Rio Grande do Sul. Anthropic alterations such as the conversion of wetlands into agricultural areas or water and soil contamination by pollutants may compromise the establishment and survival of this species. Nickel (Ni) is an essential nutrient for plants but increasing levels of this metal due to pollution can cause d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
4
1
Order By: Relevance
“…Kieling-Rubio et al (2010) observed that 50 mg L −1 of hexavalent chromium also had a signifi cant negative impact on R. diphyllum germination. Th ose same authors later found that nickel also reduced R. diphyllum spore germination, although the germination rate at 100 mg L −1 was still 46%, higher than that observed here for the same concentration of copper (Kieling-Rubio et al 2012).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Kieling-Rubio et al (2010) observed that 50 mg L −1 of hexavalent chromium also had a signifi cant negative impact on R. diphyllum germination. Th ose same authors later found that nickel also reduced R. diphyllum spore germination, although the germination rate at 100 mg L −1 was still 46%, higher than that observed here for the same concentration of copper (Kieling-Rubio et al 2012).…”
Section: Discussioncontrasting
confidence: 60%
“…Hexavalent chromium has also been shown to be toxic to R. diphyllum, stunting the growth of roots and leaves, at concentrations ≥ 3.2 mg L −1 (Kieling-Rubio et al 2010). Kieling-Rubio et al (2012) found that the primary roots, primary leaves and secondary leaves of R. diphyllum were all signifi cantly shorter when grown in solutions with nickel concentrations of 3.2 or 4.8 mg L −1 than when grown in a nickel-free solution, and that the leaves of plants grown in the 4.8 mg L −1 solution exhibited chlorosis and necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to the same concentration of hexavalent chromium also caused a significant decrease in megaspore germination, which was approximately 25% (Kieling-Rubio et al, 2010). Increasing concentrations of nickel (0.05 to 100 mg L -1 ) were also associated with a decrease in germination percentage from 75 to 45% (Kieling-Rubio et al, 2012). Lower germination percentages (of approximately 49%) were also observed in megaspores exposed to 50 mg L -1 copper (Cassanego et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…Hexavalent chromium was toxic for this species at concentrations at or above 3.2 mg L -1 , leading to reduction in root and leaf growth (Kieling-Rubio et al, 2010). The length of roots, primary and secondary leaves was also shorter in sporophytes exposed to nickel concentrations of 3.2 and 4.8 mg L -1 than in sporophytes not exposed to nickel (Kieling-Rubio et al, 2012). Cassanego et al (2013) observed significant negative effects on the development of R. diphyllum sporophytes grown in media with copper concentrations of 5 mg L -1 and higher.…”
Section: +mentioning
confidence: 92%